PLANT COMMUNITY AND SOIL RELATIONSHIP FOLLOWING WILDFIRES FROM NUEES ARDENTES ON MT. MERAPI - Sutomo Sutomo; Dini Fardila (SEAMEO BIOTROP, 2012)
At a local scale, vegetation patterns are known to have strong relationships with edaphic factors. In the case of Mt. Merapi volcanic eruption, studies on the relationships between edaphic factors and plant community composition and distribution following the nuees ardentes-ignited wildfires will provide valuable information on post-disturbance secondary successional processes. We collected soil and vegetation data from five different ages of nuees ardentes fire-affected secondary succession forests and one un-affected forest. Our results showed significant correlation of species composition and edaphic factors among sites of secondary forests. Nitrogen and soil water content were found to be the important factors in structuring species composition in the youngest site, where the N-fixing legume species such as Calliandra callothyrsus was found to be dominant. CCA ordination also revealed strong negative correlation between nitrogen content and legume group, while non-legume group were positively correlated with other edaphic factors such as phosphor and potassium. These findings suggested that changes in soil properties due to recovery of this system after volcanic eruption correlated with plant community composition and can be crucial factors in driving the successional trajectory. Understanding ecosystem reassembly process and trajectory of succession will improve how we approach the restoration of Mt. Merapi ecosystem.